2012
DOI: 10.1007/s10236-012-0564-2
|View full text |Cite
|
Sign up to set email alerts
|

Eddy diffusivity derived from drifter data for dispersion model applications

Abstract: Ocean transport and dispersion processes are at the present time simulated using Lagrangian stochastic models coupled with Eulerian circulation models that are sup- plying analyses and forecasts of the ocean currents at unprecedented time and space resolution. Using the Lagrangian approach, each particle displacement is described by an average motion and a fluctuating part. The first one represents the advection associated with the Eulerian current field of the circulation models while the second one describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…In several other studies (e.g. Gästgifvars et al, 2006;Kjellsson and Döös, 2012;De Dominicis et al, 2012), simulated marine surface currents were found to be too small, possibly also due to insufficient resolution of the marine surface layer. As a side effect, predictions may be particularly good when marine currents and winds are nearly parallel (Gästgif-vars et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In several other studies (e.g. Gästgifvars et al, 2006;Kjellsson and Döös, 2012;De Dominicis et al, 2012), simulated marine surface currents were found to be too small, possibly also due to insufficient resolution of the marine surface layer. As a side effect, predictions may be particularly good when marine currents and winds are nearly parallel (Gästgif-vars et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, as sea ice, especially compact pack ice, does not behave as a turbulent fluid, the stochastic term to be used for sea ice should not be taken to represent the same underlying physical processes as in the ocean, and it therefore may have a different form or be scaled with a different coefficient. In this section, we follow an approach that is frequently used for oceanic drifters (e.g., Dominicis et al, 2012). This approach consists of applying the diffusion analysis to observed and simulated trajectories to determine how the mean and fluctuating motion are represented and how unresolved physics could be taken into account.…”
Section: Diffusion Analysis On Observed and Simulated Sea-ice Trajectmentioning
confidence: 99%
“…The diffusion term (or in the discrete models, the Wiener process term) is either neglected or defined such that it accounts for the unresolved part of the fluctuating motion. The unresolved part of the motion could be analyzed with the methodology proposed by Dominicis et al (2012) for ocean surface tracer modeling, which consists of comparing the characteristics of the fluctuating part of observed trajectories to the ones of trajectories given by a tracer model forced by model output.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4.1, the horizontal diffusivity coefficient K h is set to zero, while simulating an oil slick from satellite, see Sect. 4.2, K h has been set to 2 m 2 s −1 in the range 1-100 m 2 s −1 indicated by ASCE (1996) andDe Dominicis et al (2012).…”
Section: Oil Spill Model Parametersmentioning
confidence: 99%